Dynorphin-Dependent Reduction of Excitability and Attenuation of Inhibitory Afferents of NPS Neurons in the Pericoerulear Region of Mice - Jüngling, Kay; Blaesse, Peter; Goedecke, Lena; Pape, Hans-Christian (Frontiers in Cellular Neuroscience, 2016)
The Neuropeptide S system, consisting of the 20-amino acid peptide neuropeptide S (NPS) and its G-protein coupled receptor (NPSR), modulates arousal, wakefulness, anxiety, and fear-extinction in mice. In addition, recent evidence indicates that the NPS system attenuates stress-dependent impairment of fear extinction, and that NPS-expressing neurons in close proximity to the locus coeruleus (pericoerulear, periLC) region are activated by stress. Furthermore, periLC NPS neurons receive afferents from neurons of the centrolateral nucleus of the amygdala (CeL), of which a substantial population expresses the kappa opioid receptor (KOR) ligand precursor prodynorphin. This study aims to identify the effect of the dynorphinergic system on NPS neurons in the periLC via pre- and postsynaptic mechanisms. Using electrophysiological recordings in mouse brain slices, we provide evidence that NPS neurons in the periLC region are directly inhibited by dynorphin A via activation of κ-opioid receptor 1 (KOR1) and a subsequent increase of potassium conductances. Thus, the dynorphinergic system is suited to inactivate NPS neurons in the periLC. In addition to this direct, somatic effect, dynorphin A reduces the efficacy of GABAergic synapses on NPS neurons via KOR1 and KOR2. In conclusion, the present study provides evidence for the interaction of the NPS and the kappa opioid system in the periLC. Therefore, the endogenous opioid dynorphin is suited to inhibit NPS neurons with a subsequent decrease in NPS release in putative target regions leading to a variety of physiological consequences such as increased anxiety or vulnerability to stress exposure.